Enhancement of Ovarian Malignancy on Clinical Contrast Enhanced MRI Studies. (13th February 2013) - Pannu, Harpreet K.; Ma, Weining; Zabor, Emily Craig; Moskowitz, Chaya S.; Barakat, Richard R.; Hricak, Hedvig
Abstract : Purpose . To assess if there is a significant difference in enhancement of high grade serous carcinoma of the ovary compared with other ovarian malignancies on clinically performed contrast enhanced MRI studies. Methods . In this institutional-review–board-approved study, two radiologists reviewed contrast enhanced MRI scans in 37 patients with ovarian cancer. Readers measured the signal intensity (SI) of ovarian mass and gluteal fat pre- and postcontrast administration. Percentage enhancement (PE) was calculated as [(post-pre)/precontrast SI] × 100. Results . Pathology revealed 19 patients with unilateral and 18 patients with bilateral malignancies for a total of 55 malignant ovaries-high grade serous carcinoma in 25/55 ovaries (45%), other epithelial carcinomas in 12 ovaries (22%), nonepithelial cancers in 8 ovaries (14%), and borderline tumors in 10 ovaries (18%). Enhancement of high grade serous carcinoma was not significantly different from other invasive ovarian malignancies (Reader 1 P = 0.865 ; Reader 2 P = 0.353 ). Enhancement of invasive ovarian malignancies was more than borderline tumors but did not reach statistical significance (Reader 1P = 0.102 ; Reader 2 P = 0.072 ). Conclusion . On clinically performed contrast enhanced MRI studies, enhancement of high grade serous ovarian carcinoma is not significantly different from other ovarian malignancies.